SPECIAL ISSUE ON AI-DRIVEN CREATIVITY AND INTELLIGENT PRACTICES IN VISUAL ARTS - Kusuma, Krishna Sankar; Kshetri, Naresh; Kabanda, Gabriel; Olabiyisi, Stephen Olatunde; Chauhan, Dipti (ShodhKosh: Journal of Visual and Performing Arts, 2025)
It is with great pleasure that we present this special issue of ShodhKosh: Journal of Visual and Performing Arts titled “AI-Driven Creativity and Intelligent Practices in Visual Arts.” As artificial intelligence and intelligent design systems increasingly shape contemporary artistic practice, visual arts are evolving into data-driven, interactive, and computational processes. The contributions in this issue examine how AI influences artistic creation, pedagogy, curation, and creative management. Reflecting interdisciplinary perspectives from visual arts, computational intelligence, emotion analytics, and education technology, this special issue documents and critically evaluates emerging paradigms, offering scholars and practitioners an academic platform to explore innovation in creative practice. Issue Editor: Dr. Krishna Sankar Kusuma Professor, AJK Mass Communication Research Centre, Jamia Millia Islamia, New Dehli, India Email: kusumakk@gmail.com Dr. Naresh Kshetri Assistant Professor (Cybersecurity), Department of Math, CS & IT, Lindenwood University, USA Email: kshetrinaresh@gmail.com Dr. Gabriel Kabanda Adjunct Professor of Machine Learning, Woxsen University, Hyderabad, India Email: gabrielkabanda@gmail.com Stephen Olatunde Olabiyisi Professor, Department of Computer Science Ladoke Akintola University of Technology Ogbomoso, Nigeria Email: tundeolabiyisi@gmail.com Dr. Dipti Chauhan Professor & Head in the Department of Artificial Intelligence & Data Science, Prestige Institute of Engineering Management & Research, Indore, M.P., India Email: diptichauhan09@gmail.com